Preparation of truncated tissue factor antineuropilin-1 monoclonal antibody conjugate and identification of its selective thrombosis in tumor blood vessels. Issue 5 (June 2019) - Xu, Peilan; Zou, Mingyuan; Wang, Shengyu; Wang, Li; Wang, Lanlan; Luo, Fanghong; Wu, Ting; Yan, Jianghua
Abstract : In recent decades, selectively inducing tumor vascular thrombosis, followed by necrosis of tumor tissues has been a promising and potential anticancer strategy. In this report, we prepared a kind of vascular targeting drug that consists of anti-neuropilin-1 monoclonal antibody (anti-NRP-1 mAb) and truncated tissue factor (tTF). Anti-NRP-1 mAb could guide tTF to the surface of tumor vascular endothelial cells and lead to subsequent vascular embolization. This vascular targeting drug, which is also one of the antibody drug conjugates, was generated using a coupling method with water-soluble 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysulfosuccimide. Afterwards, in-vitro and in-vivo assays were performed to characterize its potential coagulation ability and antitumor activity. In-vitro experiments indicated that tTF-anti-NRP-1 monoclonal antibody (tTF–mAb) retained both the targeting activity of anti-NRP-1 mAb and the procoagulant activity of tTF. Live imaging system was used to assess its biodistribution and tumor-binding capability, which also yielded promising results. Furthermore, in-vivo studies showed that tTF–mAb was capable of significantly inducing tumor vascular thrombosis and inhibiting tumor growth in nude mice bearing subcutaneous xenografts, and histopathologic changes were rarely observed in normal organs.